A Phase II Study of Everolimus Plus Oral Prednisone in Patients with Metastatic Renal Cell Cancer - Lolli, Cristian (Oncologist, 2017)
LESSONS LEARNED. The combination of everolimus and low‐dose prednisone administered daily was hypothesized to prevent noninfectious pneumonitis (NIP) and mucositis, two common adverse events related to everolimus. Although mucositis was detected in only one case, all‐grade NIP occurred in four of eight cases (50%), and this was considered enough to stop accrual of the study. These data suggest the need for careful monitoring of patients receiving everolimus who are treated with corticosteroids. BACKGROUND. Everolimus is standard of care in the treatment of patients affected by metastatic renal cell carcinoma (mRCC) that has progressed after at least one previous line of treatment. Stomatitis and noninfectious pneumonitis (NIP) are common adverse events (AEs) in patients treated with everolimus. Prednisone could reduce the incidence of stomatitis, and it is commonly used to treat NIP. We hypothesized that low doses of prednisone could reduce the incidence and/or the severity of everolimus‐induced NIP and stomatitis. METHODS. We have conducted an open‐label, single‐arm, phase II trial of prednisone 5 mg b.i.d. added to everolimus 10 mg/day in patients with mRCC. We planned to evaluate the safety, tolerability, and activity of this combination in mRCC patients. We aimed to reduce incidence of drug discontinuations due to stomatitis or NIP from 25% to 10%. RESULTS. Three (38%) of the first eight patients enrolled experienced grade ≥2 pneumonitis and stopped treatment. Grade 1 stomatitis occurred in only one patient (13%). Five of eight patients experienced disease progression at the 2‐month evaluation. Two patients (25%) were reported free of disease progression at 1 year of treatment. CONCLUSION. The incidence of NIP in these patients was considered too high for completing accrual of this study. These results may be of interest for investigating the pathogenesis of NIP and suggest that patients should be carefully followed if treated with chronic corticosteroids while receiving everolimus.